The short-term effect of nitrogen and phosphorus fertilizers on cold resistance in Urtica cannabina based on transcriptomics and metabolomics analysis - Liu, Siqi; Zhang, Xiaoxue; Zhang, Guorui; Zhao, Jinmei; Zhang, Xiaoqing (Frontiers in Plant Science, 2025)
IntroductionFreezing injury in winter is a major abiotic stress that significantly limits plant growth and survival. While nitrogen and phosphorus fertilizers have been demonstrated to alleviate the impact of freezing injury in various plant species, their role of fertilizers in the cold tolerance of Urtica spp. is still unknown.MethodsThis study investigated the effects of fertilizers on the cold resistance of U. cannabina by comprehensively analyzing the physiological and biochemical indices, transcriptome, and metabolome of the U. cannabina under applications of 150 kg nitrogen ha-1 (N) and 90 kg phosphorus ha-1 (P), using “no fertilizer” (CK) as the control.ResultsThe results showed that applying nitrogen and phosphorus fertilizers reduced the malondialdehyde concentration and had much higher superoxide dismutase activity and soluble sugar and proline concentrations. Transcriptomics and metabolomics analysis revealed that applying nitrogen and phosphorus fertilizers tended to involve several critical regulatory pathways in the biosynthesis of secondary metabolites, flavonoid biosynthesis, and phenylpropanoid biosynthesis pathways. Concretely speaking, these fertilizers can affect the biosynthesis of naringenin, pinobanksin 3-acetate, galangin, and p-Coumaroyl shikimic acid and the expression of related genes to regulate the cold tolerance of U. cannabina. Moreover, through using weighted correlation network analysis (WGCNA), 4210 genes in response to nitrogen fertilizer and 5975 genes in response to phosphorus fertilizer, positively correlating with key metabolites, were identified. Several genes encoding enzymes including glucan endo-1,3-beta-glucosidase, pectinesterase, trehalase, hydroquinone glucosyltransferase, monodehydroascorbate reductase, tyrosine aminotransferase, and peroxidase were verified to be hub genes involved in the cold-stress response of U. cannabina.DiscussionOverall, these findings have laid a theoretical foundation for the highly efficient utilization of nitrogen and phosphorus in U. cannabina and provide novel insights into the regulatory network of U. cannabina in response to cold-temperature stress.